PERSEPSI IBU – IBU TERHADAP KEGIATAN ARISAN RW 013 DI KELURAHAN TANGKERANG TIMUR KECAMATAN TANAYAN RAYA KOTA PEKANBARU - Noviana Arwulan; Titi Maemunaty; Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : The formula of the problem in this research is to find out how the house wifeperception toward reguler social activity RW 013 at Kelurahan Tangkerang Timur Kecamatan Tanayan Raya Pekanbaru City. The purpose of this research is to know how their perception toward reguler social activity. This research is descriptive quantitative. The population of the research is the reguler social house wife at RW 013. The totals opopulation is 50 people. The sample is 30 respondents by using random sampling. The research instrument is questionnaire whies consists of 40 questions. The criteria of the answer are : 4 categories, very agree, agree, less agree, and disagree. The result of research is the house wife perception toward regular social activity RW 013 at Kelurahan Tangkerang Timur Kecamatan Tanayan Raya Pekanbaru is very good. It can seen data as follow : 1) regulary social sector 88,2% respondents are very agree and agree, 2) religious sector 89,8 % respondents are very agree and agree, 3) social sector 88,2% respondents are very agree and agree.Key words : Perception, House Wife, Regular sosial activity